Symposium 3: Unmasking the climate change challenge: insight from Malaysia - Ibrahim, Faiz; Ismail, Rohaida; Hassan, Noor Artika; Mohd Tohit, Nor Faiza; Shaharudin, Shazlyn Milleana (Wolters Kluwer Health, 2024)
The complex intersection of climate change and health in Malaysia presents a multifaceted challenge, encompassing vector-borne diseases, food and waterborne illnesses, leptospirosis, heat-related ailments, children’s nutrition, mental health, and the vulnerability of public health systems. Climate change intensifies the threat of vector-borne diseases, particularly dengue fever and malaria, as shifting climate patterns create ideal environments for disease vectors. This necessitates a critical reassessment of public health strategies to effectively counteract and mitigate these emerging risks. Alterations in precipitation patterns and extreme weather events contribute to a surge in food and waterborne diseases, emphasizing the immediate need for enhanced water management, sanitation practices, and food safety measures to safeguard public health. Leptospirosis, an emerging waterborne bacterial disease, requires targeted interventions and vigilant surveillance to counter its increasing prominence in the context of climate change. A neglected tropical ailment, it demands concerted efforts to prevent its spread and mitigate its impact on public health. The escalating risks of heat-related illnesses, particularly among vulnerable populations, underscore the urgent need for adaptive measures, public awareness campaigns, and policy interventions. These actions are crucial to address the health impacts associated with extreme heat events and protect community well-being. Children’s nutrition faces challenges due to climate-induced shifts in agriculture and food security, necessitating resilient nutrition programs to safeguard the health of the younger population. The often-overlooked aspect of mental health is highlighted, emphasizing the psychological impacts of climate change-induced events such as floods and extreme weather. It stresses the importance of developing mental health support systems and interventions to alleviate the growing burden on affected populations. Lastly, the vulnerability of public health systems in Malaysia is underscored, emphasizing the necessity for comprehensive adaptation and mitigation strategies. Strengthening healthcare infrastructure and fostering collaboration among policymakers, healthcare professionals, and communities are deemed essential components for building resilience and ensuring the sustained well-being of the population amidst a changing climate.